Human-Wildlife Conflicts: A Case of Local Communities in Kieni West Sub-County, Kenya - Godhard Muiruri Kariuki (Research Aspects in Biological Science Vol. 6, 2022)
Human-wildlife conflicts (HWC) have increased in frequency and severity worldwide as a result of human population growth, expansion of agricultural and industrial activities. Conflicts are more severe in areas where both human populations and wildlife live and share ecosystem services, especially around protected areas. This study focused on different forms of human wildlife conflicts experienced by local communities in Kieni West Sub-County, Kenya. This study used a descriptive survey design. 2340 households were the study’s target population, and they came from the villages of Amboni, Bondeni, and Njeng’u. Collection of data was by means of questionnaires, interview schedules, participant observations and focus group discussions. Data analysis was done using descriptive statistics, Chi-squared tests (X2) and pearson’s correlation coefficient (r) . Information from key informants was analyzed thematically. Data was presented by frequency tables, figures and pie-charts. The results of this investigation showed that local communities in Kieni County encountered various types of human-wildlife conflicts including human injuries and threats (3%), crop damage (53%), livestock predation (23%), disease transmission to livestock (16%) and property damage (5%). This study concluded that human-wildlife conflicts were significant among local communities of Kieni West Sub-County, Kenya. Consequently, farmers were unable to realize the full potential benefits from crop and the livestock production as a result of crop damage and livestock predation from different wild animals species.